Evaluation of the Impact of Leadership Training on Organizational Service Effectiveness in the Tambrauw Regency Government - Yacoba Tabita Kinho; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (International Forum of Researchers and Lecturers, 2026)
This study aims to evaluate the impact of leadership education and training on organizational service effectiveness within the Tambrauw Regency Government, Papua. Leadership training is an important instrument in developing the competencies of Civil Servants to enhance leadership capacity, managerial skills, and public service quality. However, its implementation needs evaluation to determine its impact on organizational performance and service effectiveness. This research uses a qualitative approach with descriptive analysis. The analytical framework applied is the Kirkpatrick training evaluation model, covering reaction, learning, behavior, and results. Data collection was conducted through documentation studies, policy analysis, and literature review on civil servant development and public services. The results indicate that leadership training has a positive impact on improving civil servant competencies and service effectiveness. At the reaction level, participants showed high satisfaction with training materials and methods. At the learning level, there was improvement in leadership knowledge and skills. At the behavior level, participants demonstrated more professional work attitudes, better coordination, and improved decision-making. At the results level, training contributed to improved service quality, efficiency, and innovation. However, challenges remain, including limited resources, hierarchical bureaucratic culture, and weak policy support. Therefore, strong local government commitment is needed to enhance training quality and organizational support. This study contributes to public administration research and offers practical insights for policy development.